Factors Affecting Aggressive Behavior Among Teenage Students: A Statistical Study - Kauser Shaheen; Majid Kaleem; Muhammad Abbas; Asim Iftikhar; Muhammad Ramzan (JISR on Computing, 2025)
Abstract— A person may exhibit aggressive conduct and the mental illnesses that go along with it at any stage of life, including childhood, adolescence, adulthood, and old age. Over time, there seems to have been an increase in the prevalence of aggressive conduct among children and adolescents. Aggressive behavior in the classroom was linked to low academic engagement ratings, good attitudes toward learning, friends in the classroom, and the perception of teacher support. The use of statistical modeling techniques, such as regression analysis, multivariate correlation, Variance Inflation Factor (VIF), and feature importance analysis, forms a robust foundation for identifying the key factors contributing to student hostility in this research. These methods provide meaningful insights into behavioral patterns in educational settings and have the potential to be adapted for larger datasets or different contexts. The study identifies prior aggression and traumatic experiences as the most significant predictors of aggressive behavior in school students, with relevance values of 0.1825 and 0.1822, respectively.